Retracted: Clinical study of right iliac fossa mass: experience at a rural hospital - Ramteke, Harshal B.; Singh, Harmandeep; Wagh, Dhirendra D.; Bhoyar, Rohini J. (International Surgery Journal, 2018)
The following article from International Surgery Journal ‘Clinical study of right iliac fossa mass: experience at a rural hospital’ (Int Surg J 2018;5:2311-5, DOI: http://dx.doi.org/10.18203/2349-2902.isj20182244), by Harshal B. Ramteke, Harmandeep Singh, Dhirendra D. Wagh, Rohini J. Bhoyar was published in the Volume 5, Issue 6, June 2018, has been retracted upon authors request.